2007
DOI: 10.1074/jbc.m701745200
|View full text |Cite
|
Sign up to set email alerts
|

Unique Dimeric Structure of BNip3 Transmembrane Domain Suggests Membrane Permeabilization as a Cell Death Trigger

Abstract: BNip3 is a prominent representative of apoptotic Bcl-2 proteins with rather unique properties initiating an atypical programmed cell death pathway resembling both necrosis and apoptosis. Many Bcl-2 family proteins modulate the permeability state of the outer mitochondrial membrane by forming homoand hetero-oligomers. The structure and dynamics of the homodimeric transmembrane domain of BNip3 were investigated with the aid of solution NMR in lipid bicelles and molecular dynamics energy relaxation in an explicit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
111
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(119 citation statements)
references
References 46 publications
8
111
0
Order By: Relevance
“…As shown in Fig. 6A, the model is extremely similar to the NMR structure (16,20). The RMSD of the helical region of the entire TM domain is 1.10 ± 0.36 Å and only 0.56 ± 0.17 Å when it is computed only for the region that participates in the helix−helix interaction.…”
Section: A Minimalistic Set Of Energy Functions Predicts Known Structmentioning
confidence: 56%
See 1 more Smart Citation
“…As shown in Fig. 6A, the model is extremely similar to the NMR structure (16,20). The RMSD of the helical region of the entire TM domain is 1.10 ± 0.36 Å and only 0.56 ± 0.17 Å when it is computed only for the region that participates in the helix−helix interaction.…”
Section: A Minimalistic Set Of Energy Functions Predicts Known Structmentioning
confidence: 56%
“…We tested CATM against five known homodimeric GAS right structures: glycophorin A (15), BNIP3 (16,20), and three members of the Tyrosine Receptor Kinase family, EphA1 (21), ErbB1 (EGFR) (22), and ErbB4 (23). We began testing using a simple combination of hydrogen bonding (E hb ) and van der Waals (E vdw ) to score the structural models.…”
Section: A Minimalistic Set Of Energy Functions Predicts Known Structmentioning
confidence: 99%
“…The unique structure of the TM domain suggests that BNIP3 dimers could act as proton channels in the outer mitochondrial membrane increasing ion conductance. 5 Serine 172 and histidine (His) 173 are residues that are present in the dimerization interface of BNIP3. These residues interact by hydrogen bonds and are essential for dimer formation.…”
mentioning
confidence: 99%
“…Correctness of the remaining models was assessed via comparison with the mutagenesis data. As a result, one of the final models consistent with the mutagenesis data was also in good agreement with the NMRderived structure of dimeric Bnip3 TM domain in lipid bicelles (Bocharov et al, 2007). Volynsky et al, 2010, used modeling methods in combination with ToxR assays to study dimerization of TM segments of ephrin receptor EphA1.…”
mentioning
confidence: 58%
“…Investigation of spatial structure and internal dynamics of the homodimeric TM domain of human protein BNip3 (PDB 2J5D, Bocharov et al, 2007) revealed that in the lipid bicelles the central membrane-spanning -helices of BNip3 cross at the angle of -45° and form a right-handed parallel symmetric dimer via tetrad repeat pattern S 172 H 173 xxA 176 xxxG 180 xxxG 184 (Fig. 3).…”
Section: Protein Engineering 16mentioning
confidence: 99%